In-hospital outcomes of treatment of patients with acute coronary syndrome using distal radial access - Yu. v. Mikheeva; D. S. Kurtasov; P. P. Ogurtsov; A. G. Koledinskii (Кардиоваскулярная терапия и профилактика, 2021)
Endovascular methods are leading in the treatment of patients with acute coronary syndrome (ACS). Transradial access (TRA) is traditionally used, but there are some disadvantages. Distal transradial access (dTRA) is an alternative to conventional TRA, but its outcomes in patients with ACS are controversial.Aim. To evaluate the safety and efficacy of vascular accesses, as well as in-hospital outcomes of treatment of patients with ACS using conventional TRA versus dTRA.Material and methods. This single-center, prospective, randomized study included 264 patients with ACS, which were divided into 2 groups: group 1 (n=132) — dTRA, group 2 (n=132) — TRA. The groups were comparable in the initial clinical, laboratory and angiographic characteristics.Results. During percutaneous coronary intervention, 240 drug-eluting stents were implanted in 184 patients. In 10 patients, access was converted: from dTRA to TRA in 2,3% (n=3), from dTRA to femoral  — 3,0% (n=4), from dTRA to femoral in 2,3% (n=3). The mean puncture time was 125,1±11,9 s in group 1 and 58,8±8,2 s in group 2 (p<0,00005). There was no difference in the total intervention duration as follows: 30,5±7,1 min and 29,4±4,6 min (p=0,1428), respectively. The time to hemostasis was significantly higher in the TRA group: 354,2±28,1 vs 125,4±15,3 min in group 1 (p<0,00005). When using dTRA, a lower incidence of hematomas (0,8 (n=1) vs 7,0% (n=9) (p=0,019)), spasm (5,6 (n=7) vs 13,2% (n=17) (p=0,039)) and radial artery occlusion (0,8 (n=1) vs 6,2% (n=8) (p=0,036)). The number of major adverse cardiac events (MACE) in both groups was comparable: 10,4% (n=13) and 10,1% (n=13) in group 1 and 2, respectively (p=0,932).Conclusion. The use of dTRA does not increase the total procedure duration compared to conventional TRA. The complication rate was comparable in both study groups. When dTRA was used, the incidence of local complications was significantly lower compared to conventional TRA. Thus, dTRA can be an alternative to conventional TRA, but large randomized trials are required for final conclusions.